Small and medium enterprises (SME) adjustments to information technology (IT) in trade facilitation: The South Korean experience - Junsok Yang (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2009)
This report examines how IT was incorporated into cargo clearance procedures in Korea, and what its implications are for traders, SMEs in particular. After a short introduction in Section I, Section II examines the definition of SMEs in Korea, and SMEs' role in Korean trade. In Section III, we describe the history of the adoption of IT in Korean cargo clearance. The introduction of IT to cargo clearance procedures in Korea can be roughly divided into two stages. The first stage includes the implementation of: Preparation for Customs Clearance Automation (1980s-1992), EDI Customs Clearance Automation Six Year Plan (1992-1997), Establishment of Paperless Customs Clearance System (1997-2001); and the Plan for Establishment of Infrastructure for Information Technology and Knowledge Management (2001-2003). The main accomplishment of the first stage was a Value Added Network / Electronic Data Interchange (VAN/EDI) which linked KCS and traders in 1996. The system was subsequently expanded so that traders could access the system through the Internet. The second stage begun in 2003, and has nearly reached completion in 2008. The goal of the second stage is to build an e-trade system where IT is used at every stage of trade, encompassing not only government-business (traders) transactions such as cargo clearance, but all trade-related transactions including business-business transactions as well. This second stage involves the establishment of an e-trade network and uTradeHub, which ties not only government with traders, but other trade-related organizations and private agencies such as shippers, insurers, banks and financial institutions. These projects were carried out with considerations for SMEs in mind. Section IV describes the results of the adoption of IT into cargo clearance. We find that IT has significantly lowered costs and sped up the cargo clearance process. Section V includes some case examples of individual firms which use the e-trade network for cargo clearance. Lastly, section VI tries to draw some lessons for other countries which seek to adopt IT into cargo clearance. These lessons include: 1) Adopting IT to cargo clearance must be a part of a comprehensive customs procedure reform. 2) Legal framework must accompany the adoption of IT and e-trade 3) Single network and single standard may be more useful than variety 4) Keep It Simple 5) The e-trade system and paperless trade system is meant to be used by the widest number of people. 6) Trust must be built between SMEs and government agencies. 7) Usefulness of e-trade will increase exponentially when more countries join.
Keywords: 330; KMU; Informationstechnik; Außenhandel; Südkorea